Interactive system implementation to encourage reading in vulnerable community children (2017)
This paper describes the process for the development of an interactive educational system for the children of the Siloé neighborhood of the Cali city, Colombia. Starting from the purpose of mitigating negative influences within the context of the neighborhood, this project seeks to encourage curiosity in children by reading as a core competency for their future, through a technological solution that sparks the interest of this community. In order to define the characteristics of the system, an inquiry process was carried out to identify the needs and charac‐ teristics of the target audience, as well as their preferences about technological devices and applications used by them. Once the main features were defined, the process of prototyping began based on sketches that evolved into prototypes of low and high fidelity. Then, those prototypes were evaluated with potential users, applying usability evaluation methods in order to collect information about the system and make the necessary adjustments to get an usable final product.